Faktor-Faktor Yang Mempengaruhi Opini Audit GoingConcern Pada Perusahaan Manufaktur Dan PerusahaanNon Manufaktur (Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun2013-2015) - Fatimah, Mernafita; , Fauzan, SE, Ak, MSi (2017)
Opinion audit going concern is an audit opinion issued by the auditor to determine whether the company can maintain its viability. Going Concern is one of the most important concepts based on financial reporting to establish viability of the company. The purpose of this study was to determine the effect of audit quality, the proportion of independent commissioner board, the previous year's audit opinion, the company's growth and size of the company the acceptance opini audit going concern. This research was conducted at the manufacturing and non-manufacturing companies listed at Indonesia Stock Exchange in 2013-2015. The population is 684 companies. The sample in this study are 162 companies that obtained by purposive sampling method. The result of this research is the quality of the audit, the proportion of independent commissioner board affect the acceptance of the opini audit going concern, whereas for the previous year's audit opinion, the growth of the company and the size of the company does not Affect the acceptance opini audit going concern.